Approximation of classes of periodic functions of several variables with given majorant of mixed moduli of continuity - Fedunyk-Yaremchuk, O.V.; Hembars'ka, S.B. (Carpathian Mathematical Publications, 2021)
In this paper, we continue the study of approximation characteristics of the classes B^Ω_p,θ of periodic functions of several variables whose majorant of the mixed moduli of continuity contains both exponential and logarithmic multipliers. We obtain the exact-order estimates of the orthoprojective widths of the classes B^Ω_p,θ in the space L_q, 1≤ p<q<∞, and also establish the exact-order estimates of approximation for these classes of functions in the space L_q by using linear operators satisfying certain conditions.